FEAUTURES OF INTRODUCTION OF FOREIGN MEDICINE STUDENTS TO THE UNIVERSITY EDUCATION PROCESS - Kudratova Zebo Erkinovna; Shirinov Xusеyn Isrofiovich (Journal of new century innovations, 2023)
Annotation. The problem of providing complete higher education in the training of qualified specialists is currently an urgent task for medical universities in all developed countries of the world [3].